Razumevanje bihevioralnih namera usvajanja internet bankarstva: Indijska perspektiva - Malik, Garima; Singh, Dharmendra; Stakić, Nikola (The European Journal of Applied Economics, 2022)
Internet banking gives banks colossal advantages as far as cost reserve funds, better client connections, and separate contributions from the opposition. This study expects to recognize the components that essentially influence the intention of bank clients to utilize Internet banking administrations in India. The examination proposed a complete model called Internet Banking Adoption in India, which was an implicit part based on the "Brought together Theory of Acceptance and Use of Technology" (UTAUT) and three extra factors that were recognized as setting delicate. A self-made survey with 100 samples on impact of behavioural intention to adopt Internet Banking was conducted using surveys available on the Internet. For further analysis, statistical tool like Chi-Square, correlation and regression was performed on SPSS software. According to the TAM Model, perceived trust, perceived risk and perceived ease of use was taken into consideration to rate the behavioural intention for adopting Internet Banking in day-to-day life.